Concurrent left ventricular myocardial diffuse fibrosis and left atrial dysfunction strongly predicts incident heart failure and all-cause mortality. (25th January 2023) - Aung, N; Wong, M Y Z; Vargas, J D; Naderi, H; Sanghvi, M M; Raisi-Estabragh, Z; Suinesiaputra, A; Bonazzola, R; Attar, R; Ravikumar, N; Hann, E; Neubauer, S; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation Academy of Medical Sciences Background: LV myocardial interstitial fibrosis has been reported to influence LA morphology and function via LV remodelling and diastolic dysfunction. However, this association, as well as their combined influence on clinical outcomes remains poorly characterised. Aim: To evaluate the relationship between left ventricular (LV) fibrosis quantified by native T1 times and left atrial (LA) global and phasic function and their impact on clinical outcomes. Methods: A total of 40, 818 UK Biobank participants with cardiovascular magnetic resonance data were included. Native T1 mapping was performed using Shortened Modified Look-Locker Inversion recovery sequence with global myocardial T1 estimated by an automatic segmentation framework. Ten parameters of LA phasic function were calculated from normalised LA volume-time curves derived by a three-dimensional sparse active shape model. LV parameters (mass, end-diastolic volume, and ejection fraction) were extracted by a fully convolutional neural network. Multivariable regression models were used to assess the associations between T1 and LA parameters. Lastly, survival analysis was performed to assess the interplay between T1, LA function and incident heart failure, atrial fibrillation, major adverse cardiovascular event (MACE) and all-cause mortality. Results: The mean age of study population was 64.0 ± 7.7 years; 47.8% were men. Higher T1 values were associated with larger LA minimum size (Beta= 0.89ml per 100ms; 95% confidence interval (CI) = 0.62, 1.17), and lower LA global emptying fraction (Beta= -0.012 per 100ms; CI= -0.015, -0.010), LA reservoir function (Beta= -0.060 per 100ms; CI= -0.083, -0.037) and LA booster function (Beta= -0.014 per 100ms; CI= -0.017, -0.011). Among LA phasic functional parameters, LA booster function is most strongly associated with T1. Survival analysis revealed concurrent high T1 and low LA function had a significant influence on incident heart failure (Hazard Ratio [HR] = 2.99; CI=1.91, 2.01), atrial fibrillation (HR = 4.86; CI=3.51-6.54), MACE (HR = 1.86; CI = 1.36-2.54) and all-cause mortality (HR = 1.86; CI=1.22-2.82) compared to either parameter alone, even after accounting for LV parameters (Figure 1). Conclusion: This is the first study to robustly demonstrate the associations between myocardial diffuse fibrosis and reduced LA global and phasic functional measurements. We reveal the independent prognostic role of high T1 values accompanied by low LA function in predicting adverse clinical outcomes in a general population. These findings advance our understanding of the relationships between myocardial fibrosis and LA biomechanics at an early, subclinical stage, and highlight the additive value of incorporating these biomarkers into clinical decision making. Figure 1